A Review of Human Papillomavirus Prevalence and Cervical Cancer in Myanmar - Tay Za Kyi Win; Kate Simms; Myint Myint Thinn; Khaing Nwe Tin; Soe Aung; Eleonora Feletto; Deborah Bateson; Karen Canfell (Journal of Epidemiology and Global Health)
Abstract Background Myanmar is estimated to have one of the highest cervical cancer incidence and mortality rates in Asia. There have been limited screening and treatment services for cervical cancer in Myanmar. In this context, to support cervical cancer elimination, understanding the current burden of cervical cancer in the country is crucial. This review aims to synthesize the evidence on the epidemiology of cervical cancer in Myanmar. Methods We used the Joanna Briggs Institute approach for systematic review of observational epidemiological studies to conduct a comprehensive review of burden of human papillomavirus (HPV), precancerous cervical lesions, key co-factors and cervical cancer in Myanmar. Embase, Global Health, Medline, and local databases were searched to May 31, 2024. Results Regional population-based cancer registries from Nay Pyi Taw and Yangon reported age-standardized incidence rates of cervical cancer of 19.3 (in 2018) and 14.1 (during 2013–2017) per 100 000 females, respectively. Meta-analyses were conducted to estimate HPV prevalence among the general female population (18–65 years) as 4% [95% Confidence Interval (CI): 3–5%] in the community-based and 11% [95% CI: (4–21%)] in outpatient clinic screening. Among HIV-positive women, HPV prevalence was reported at 30.1%. The most common HPV types in HPV-positive cervical cancers were HPV 16 (60–85.7%) and HPV 18 (14.8–20%). The prevalence of key co-factors included HIV infection (0.7% in the general female population and 8.3% in female sex workers), tobacco use in females (smoking: 8.4% and smokeless: 24.1%), high parity (4.99 births per married woman) and early aged pregnancy (33 births per 1000 adolescent females). Conclusions The cervical cancer incidence rates reported from two regional cancer registries in Myanmar are high relative to those reported in countries across Asia. An estimated one in nine to one in 25 women in Myanmar is infected with HPV, which is broadly concordant with regional estimates. A high prevalence of key co-factors for cervical cancer, combined with limited screening and treatment services, may increase the risk of progression to invasive cancers among HPV infected women. Consequently, Myanmar is likely to bear a substantial burden of cervical cancer.